Urban servitudes in Ancient Rome and their influence on the city development - Grin, Irina (project baikal, 2023)
Urban servitudes, as part of Roman law, became a legislative necessity for resolving disputes and regulating complex relationships. Urban servitudes were of great importance in reducing conflicts between city residents. After the fall of the Roman Empire and the medieval redistribution of land, servitudes have firmly entered the system of European urban planning.
Keywords: Ancient Rome; servitudes; easements; city residents and city authorities; Republican Rome; Roman Empire; history of urban planning